Urethral stones and benign prostatic hyperplasia: Presentation of a rare case - Özdeş, Alper; Cantürk, Rıdvan; Pirinçci, Necip (My University, 2025)
An 86-year-old male patient presented with urinary incontinence, fever, weakness, and hematuria. Investigations revealed benign prostatic hyperplasia (BPH) with multiple bladder stones and several stones in both the anterior and posterior urethra, without causing acute urinary retention (AUR). During the same session, endoscopic urethral stone treatment, open transvesical prostatectomy, and cystolithotomy were performed. Benign prostatic hyperplasia and urethral stones can lead to acute urinary retention. However, in this case, the patient did not develop acute urinary retention despite having both benign prostatic hyperplasia and multiple urethral stones at the same time. This case demonstrates that multiple causes of urinary obstruction may coexist without resulting in AUR. It also highlights the feasibility of combining different surgical techniques in treatment. Factors such as the concomitant comorbidities, stone and prostate size and location, condition of the patient, and duration of the symptoms must be considered to establish an appropriate treatment strategy.
Keywords: Surgery; Bladder; Urethra; Stone; Benign prostate hyperplasia